Timing of Water Deficit Limits Maize Kernel Setting in Association With Changes in the Source-Flow-Sink Relationship - Li, Yebei; Tao, Hongbin; Zhang, Bingchao; Huang, Shoubing; Wang, Pu (Frontiers in Plant Science, 2018)
Kernel setting of maize varied greatly due to the timing and intensity of water deficit that can limit leaf productivity (source), assimilates translocation (flow), and yield formation (sink). To explain the decline in kernel setting of maize under water deficit from the perspective of source-flow-sink, a 3-year experiment was conducted under rain shelter, including five water regimes, well irrigation (CK), water deficit by withholding irrigation during 6 to 8-leaf stage (V6-8), 9- to 12-leaf stage (V9-12), 13-leaf stage to tasseling (V13-T), and silking to blister (R1-2), respectively. Water deficit effects on kernel setting initiated when water deficit occurred at V9 and became more distinct with time. Kernel weight reduced by 12% and 11% under water deficit occurring at V9-12 and V13-T, respectively, as a consequence of reduced leaf area (limited source) and vascular bundle size and number in ear pedicle (limited assimilate flow). Water deficit prior to and nearly flowering stage significantly reduced ear kernel number, i.e. 14% and 19% less in V13-T and R1-2 than that of CK, respectively, reflecting a relatively smaller sink under water deficit conditions. After re-watering, water deficit before or at flowering stage still had residual effects on the grain filling in the late growth period. Grain filling rate reduced under V9-12 water deficit, grain filling duration shortened under R1-2 water deficit, and both negative effects occurred under V13-T water deficit. This study clearly indicated that (1) water deficit during vegetative organ rapid growth period not only limited leaf source development and assimilate flow, but also slowed down kernel development, and (2) water deficit nearly before and during flowering reduced kernel sink, both of which can retard grain filling, and thus reduce maize yield. Results in this study have an important implication in guiding irrigation practice in irrigated maize or managing sowing time in rainfed maize to dis-synchronize water deficit and water deficit sensitive stage.